Zinc gallate-based near-infrared long-afterglow fluorescent material as well as preparation process and application thereof

By co-doping lithium and germanium/titanium elements into zinc gallate-based near-infrared long afterglow fluorescent materials, a new fluorescent material system was formed, which solved the problems of insufficient luminous intensity and short afterglow life of existing long afterglow materials, and achieved a longer luminous effect, which was suitable for biomedical imaging.

CN120424653APending Publication Date: 2025-08-05UNIV OF JINAN
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510362904.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The existing long afterglow materials are insufficient in the field of biomedical imaging and have fast attenuation of the afterglow life, making it difficult to meet the luminescence demand for longer periods.

Method used

Zn1-xLixGa2-xMxO4:yCr3+ is used to form a new fluorescent material system by co-doping lithium element (Li) and germanium/titanium element (M), increasing the number of traps and trap depth, adjusting the crystal structure and band gap, and enhancing the emission performance of Cr3+ ions.

Benefits of technology

It significantly improves afterglow life, increases luminescence time and luminescence intensity, effectively inhibits afterglow attenuation, and meets the needs of biomedical imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120424653A_ABST
    Figure CN120424653A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of fluorescent materials, and particularly discloses a zinc gallate-based near-infrared long-afterglow fluorescent material as well as a preparation process and application of the zinc gallate-based near-infrared long-afterglow fluorescent material. The composition of the fluorescent material is Zn1-xLixGa2-xMxO4: yCr < 3 + >, y is more than or equal to 0.001 and less than or equal to 0.005, x is more than or equal to 0.1 and less than or equal to 0.5 when M is Ge < 4 + >, and x is more than or equal to 0.1 and less than or equal to 0.9 when M is Ti < 4 + >. According to the invention, after the Li element is used for replacing part of Zn element in a zinc gallate matrix and the Ge element is used for replacing part of Ga element, the luminescence mechanism and luminescence performance of the fluorescent material are greatly influenced, so that the material crystal structure and matrix band gap can be adjusted on the premise of maintaining charge conservation of the fluorescent material, and the luminous efficiency of the fluorescent material is improved. The targets of full-wave-band excitation and ultra-long afterglow life are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fluorescent material preparation, and in particular to a zinc gallate-based near-infrared long-afterglow fluorescent material and a preparation process and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] In recent decades, biomedical imaging technology has gained increasing attention from researchers due to its simplicity, non-invasiveness, real-time nature, and ability to detect pathological changes in diseased tissues at an early stage. Its applications in cancer imaging, immunology, transplant biology, infectious diseases, cardiovascular disease, and central nervous system disorders have been extensive. Molecular imaging technology, the foundation of bioimaging, utilizes molecular probes and signals to reveal physiological or pathological changes in tissues and cells within living organisms, enabling qualitative and quantitative studies.

[0004] Fluorescence imaging is a molecular imaging technique that uses an external excitation light source to illuminate fluorescent groups (such as organic dyes, fluorescent protein GFP, and nanoluminescent materials) to produce fluorescence. Near-infrared long-lasting luminescent materials, as key supporting materials for fluorescence imaging, are receiving increasing research and exploration. With the advancement of modern medical technology, the demand for in vivo imaging is becoming increasingly stringent. Long-lasting luminescent materials are materials that continue to emit light even after excitation ceases. Unlike conventional luminescent materials, upon excitation, some electrons in long-lasting luminescent materials transition to the conduction band and emit light immediately, while others are trapped in trap levels through processes such as non-radiative relaxation. Upon subsequent thermal agitation, they return to excited states, resulting in prolonged luminescence. However, a key issue with current long-lasting luminescent materials is their insufficient luminescence intensity and rapid decay of the afterglow lifetime, making it difficult to achieve extended luminescence durations, limiting their application in biomedical imaging. Summary of the Invention

[0005] To address these issues, the present invention provides a zinc gallate-based near-infrared long-lasting fluorescent material, its preparation process, and its application. This material features a greater number of traps and a deeper trap depth, enabling it to store more energy and effectively extending the fluorescent material's luminescence duration. Specifically, the technical solution of the present invention is as follows.

[0006] First, the present invention provides a zinc gallate-based near-infrared long-lasting fluorescent material, which is composed of Zn 1-x Li x Ga2- x M x O4: y Cr 3+ , where 0.001≤ y ≤0.005, and when the M is Ge 4+ When 0.1≤ x ≤0.5, when M is Ti 4+ When 0.1≤ x ≤0.9.

[0007] Secondly, the present invention discloses a preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material, comprising the following steps: (1) According to the Zn 1-x Li x Ga 2-x M x O4: y Cr 3+ A zinc source, a lithium source, a gallium source, a M source, and a chromium source are weighed as raw materials in a stoichiometric ratio, and these raw materials are mixed and ground to obtain a mixed powder for later use.

[0008] (2) The mixed powder is calcined and then cooled to room temperature to obtain the fluorescent material.

[0009] Furthermore, in step (1), the zinc source includes at least one of zinc carbonate (ZnCO3), zinc oxide (ZnO), and the like.

[0010] Furthermore, in step (1), the lithium source includes at least one of lithium carbonate (Li2CO3), lithium oxide (Li2O), etc.

[0011] Furthermore, in step (1), the gallium source includes gallium oxide (Ga2O3) and the like. The chromium source includes chromium trioxide (Cr2O3) and the like.

[0012] Furthermore, in step (1), among the M sources, the germanium (Ge) source includes germanium dioxide (GeO2) and the like, and the titanium (Ti) source includes titanium oxide (TiO2) and the like.

[0013] Furthermore, in step (1), the grinding time is 30-40 min, and the grinding rate is 1500-2000 rpm.

[0014] Furthermore, in step (2), the calcination treatment is carried out by first heating the temperature to 600-900°C for pre-calcination for 3-5 hours, then cooling the temperature to room temperature, then reheating the temperature to 1000-1200°C for 3-5 hours, and then cooling the temperature to room temperature.

[0015] Finally, the present invention discloses the application of the zinc gallate-based near-infrared long-afterglow fluorescent material in the fields of temperature warning signs, biomedical imaging, night vision display, lighting, etc.

[0016] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: The fluorescent material of the present invention is co-doped with lithium (Li) and M (Ge / Ti) elements in the zinc gallate matrix, and the new system Zn is formed by replacing part of the Zn element with Li element and part of the Ga element with Ge / Ti element. 1-x Li x Ga 2-x M x O4: y Cr 3+ Fluorescent materials greatly affect the luminescence mechanism and luminescence performance of long afterglow materials, so that the fluorescent materials of the present invention can adjust the material crystal structure and matrix band gap under the premise of maintaining charge conservation, achieving the goal of full-band excitation and ultra-long afterglow life. This is because the present invention uses Li + / M 4+ Doping not only brings Li Zn ′ and M Ga • Octahedral distortion defects significantly reduce the symmetry of the CrO6 octahedron, narrow the band gap, lower the conduction band bottom, deepen the defect trap, and enhance the Cr 3+ N2 line of ions (distorted lattice Cr 3+ ion) emission. + / M 4+ Doping leads to Li Zn ′-Ge Ga • 、Li Zn ′-Ti Ga • The number of defect clusters increases, the trap energy level splits, and the electron transfer between deep and shallow trap energy levels is reduced, making the deep trap energy level close to Cr 3+ Ionic 2 This new system not only significantly improves the afterglow lifetime, but also increases the depth of the trap energy level, allowing it to store more electrons. When the excitation stops, the electrons are slowly released from the trap energy level, effectively suppressing the rate of afterglow decay and increasing the luminescence time and intensity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 The following are X-ray diffraction patterns of the fluorescent materials prepared in Examples 1 to 5.

[0019] Figure 2 The excitation spectra of the fluorescent materials prepared in the following Examples 1 to 5 and the blank control group are shown.

[0020] Figure 3 The emission spectra of the fluorescent materials prepared in the following Examples 1 to 5 and the blank control group are shown.

[0021] Figure 4 The long afterglow luminescence spectra of the fluorescent materials prepared in the following Examples 1 to 5 and the blank control group are shown.

[0022] Figure 5 The graph shows the decay of the afterglow brightness of the fluorescent materials prepared in the following Example 5 and the blank control group over time after being excited.

[0023] Figure 6 This is a test chart of the ability of the fluorescent materials prepared in the following Example 5 and the blank control group to release electrons captured in the trap energy level at different temperatures.

[0024] Figure 7 The following are the X-ray diffraction patterns of the fluorescent materials prepared in Examples 6 to 10.

[0025] Figure 8 The long afterglow luminescence spectra of the fluorescent materials prepared in the following Examples 6 to 10 are shown. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present invention only and are not intended to limit the scope of the invention. The experimental methods in the following examples, for which specific conditions are not specified, are generally performed under conventional conditions or as recommended by the manufacturer.

[0027] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents and raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents and raw materials used in the present invention are used in accordance with conventional methods in the art or in accordance with the product instructions.

[0028] In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention. The technical solution of the present invention will now be further described with reference to the accompanying drawings and specific embodiments.

[0029] Example 1 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn0.9 Li 0.1 Ga 1.9 Ge 0.1 O4: 0.005Cr 3+ The stoichiometric ratio ( x = 0.1). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, germanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material into a ball mill jar containing an appropriate amount of anhydrous ethanol. Then, place the jar in a planetary ball mill and grind at 1800 rpm for 30 minutes. Discard the mixed powder.

[0030] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 900°C at a rate of 5°C / min and pre-fired for 4 hours, then cooled to room temperature in the furnace. It is then reheated to 1200°C and kept at this temperature for 4 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0031] Example 2 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.8 Li 0.2 Ga 1.8 Ge 0.2 O4: 0.003Cr 3+ The stoichiometric ratio ( x = 0.2). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, germanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material into a ball mill jar containing an appropriate amount of anhydrous ethanol. Then, place the jar in a planetary ball mill and grind at 1500 rpm for 40 minutes. Discard the mixed powder.

[0032] (2) The mixed powder was poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It was first heated to 900°C at a rate of 5°C / min and pre-fired for 4 hours, then cooled to room temperature in the furnace. It was then reheated to 1100°C and kept at this temperature for 3.5 hours. After completion, it was cooled to room temperature in the furnace to obtain the fluorescent material.

[0033] Example 3 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.7 Li 0.3 Ga 1.7 Ge 0.3 O4: 0.002Cr 3+ The stoichiometric ratio ( x=0.3). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, germanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material in a ball mill containing an appropriate amount of anhydrous ethanol. Then, place the ball mill in a planetary ball mill and grind at 2000 rpm for 35 minutes. Discard the mixed powder.

[0034] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 800°C at a rate of 5°C / min and pre-fired for 4.5 hours, then cooled to room temperature in the furnace. It is then reheated to 1000°C and kept at this temperature for 4.5 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0035] Example 4 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.6 Li 0.4 Ga 1.6 Ge 0.4 O4: 0.001Cr 3+ The stoichiometric ratio ( x =0.4). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, germanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material in a ball mill containing an appropriate amount of anhydrous ethanol. Then, place the ball mill in a planetary ball mill and grind at 1800 rpm for 30 minutes. Discard the mixed powder.

[0036] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 900°C at a rate of 5°C / min and pre-fired for 3 hours, then cooled to room temperature in the furnace. It is then reheated to 1200°C and kept at this temperature for 3 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0037] Example 5 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.5 Li 0.5 Ga 1.5 Ge 0.5 O4: 0.004Cr 3+ The stoichiometric ratio ( x=0.5). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, germanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material into a ball mill jar containing an appropriate amount of anhydrous ethanol. Then, place the jar in a planetary ball mill and grind at 1800 rpm for 30 minutes. Discard the mixed powder.

[0038] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 600°C at a rate of 5°C / min and pre-fired for 5 hours, then cooled to room temperature in the furnace. It is then reheated to 1000°C and kept at this temperature for 5 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0039] Figure 1 The X-ray diffraction patterns (XRD) of the fluorescent materials prepared in Examples 1 to 5 show that the fluorescent materials prepared in the above examples have Li + 、Ge 4+ It was successfully doped into ZnGa2O4, and these fluorescent materials have good crystallinity, high purity, and no impurities.

[0040] Figure 2 For Examples 1 to 5 and the blank control group (i.e. x =0) is shown in the PLE spectrum of the fluorescent material prepared. It can be seen that the excitation spectrum obtained under 710nm emission monitoring mainly includes four peaks: 262nm, 300nm, 410nm and a broadband excitation peak near 560nm, ranging from 500nm to 580nm. The excitation peak at 262nm belongs to the transition from valence band to conduction band, corresponding to the Cr 3+ The excitation peak at 300nm belongs to 4 The dd transition of A2→4T1 (4P) is due to the transition from valence band to conduction band. 4 A2→ 4 T1 (4P) has spectral overlap, so the excitation peak at 300nm cannot be clearly observed. 4 A2→ 4 The dd transition of T(14F) corresponds to 560nm 4 A2→ 4 T2 (4F) dd transition. Excited to 4 A2→ 4 T1 (4P), 4 A2→ 4 T1 (4F), 4 A2→ 4 The electron at T2 (4F) returns to 2 E energy level, further transitions back to the ground state under the action of excitation light4 A2 energy level.

[0041] Figure 3 For Examples 1 to 5 and the blank control group (i.e. x =0) under 262nm light excitation. The R line corresponds to the emission peak around 690nm; the Cr 3+ ion 2 E→ 4 A2 energy level transition. At this time, Cr 3+ Entering the crystal, replacing Ga 3+ Occupies the octahedral gap, Zn 2+ In the tetrahedral gap without lattice distortion. ZnGa2O4: Cr 3+ There are about 3% antisite defects in the spinel structure, that is, 3%Ga 3+ Occupancy of Zn 2+ Tetrahedral position; 3% Zn 2+ Occupy Ga 3+ The octahedral position of Cr 3+ Substitute Ga in the antisite defect 3+ , resulting in lattice defects in the unit cell, making the corresponding 2 The E energy level is higher than that in the case of no lattice distortion. 2 E energy level, the emission peak is slightly red-shifted, showing as N line. 3+ The radius is slightly smaller than Ga 3+ Radius, when Cr 3+ After entering the octahedral position, the lattice will shrink to a certain extent, resulting in 2 The E level splits. In addition, it can be seen that Figure 4 For Examples 1 to 5 and the blank control group (i.e. x =0) prepared by the long afterglow luminescence spectrum of the fluorescent material. It can be seen that: compared with the blank control group, the fluorescent materials of Examples 1 to 5 are + 、Ge 4+ Co-doping effectively improves the afterglow lifetime, increases the depth of the trap energy level, and stores more electrons. When the excitation stops, the electrons are slowly released from the trap energy level, effectively suppressing the rate of afterglow decay and increasing the luminescence time and intensity.

[0042] Figure 5 For Example 5 and the blank control group (i.e. x =0) after being excited. It can be seen that compared with the blank control group, the Examples 1 to 5 are + 、Ge 4+ Co-doping significantly improves the afterglow life of the fluorescent material, which is consistent with the above Figure 4The test results are consistent.

[0043] Figure 6 For Example 5 and the blank control group (i.e. x = 0) at different temperatures. As can be seen, the brightness of Example 5 remains consistently higher than that of the blank control group as the temperature increases, demonstrating that the fluorescent material of Example 5 significantly outperforms the blank control group in its ability to capture electrons. This is because, under temperature excitation, electrons trapped in deep trap levels in the fluorescent material of Example 5 gradually transition back to excited states and then to the ground state, resulting in a more pronounced afterglow phenomenon.

[0044] Example 6 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.9 Li 0.1 Ga 1.9 Ti 0.1 O4: 0.005Cr 3+ The stoichiometric ratio ( x = 0.1). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, titanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material into a ball mill jar containing an appropriate amount of anhydrous ethanol. Then, place the jar in a planetary ball mill and grind at 1800 rpm for 30 minutes. Discard the mixed powder.

[0045] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 900°C at a rate of 5°C / min and pre-fired for 4 hours, then cooled to room temperature in the furnace. It is then reheated to 1200°C and kept at this temperature for 4 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0046] Example 7 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.7 Li 0.3 Ga 1.7 Ti 0.3 O4: 0.003Cr 3+ The stoichiometric ratio ( x = 0.3). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, titanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material into a ball mill jar containing an appropriate amount of anhydrous ethanol. Then, place the jar in a planetary ball mill and grind at 1800 rpm for 30 minutes. Discard the mixed powder.

[0047] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 900°C at a rate of 5°C / min and pre-fired for 4 hours, then cooled to room temperature in the furnace. It is then reheated to 1200°C and kept at this temperature for 4 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0048] Example 8 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.5 Li 0.5 Ga 1.5 Ti 0.5 O4: 0.002Cr 3+ The stoichiometric ratio ( x = 0.5). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, titanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material into a ball mill jar containing an appropriate amount of anhydrous ethanol. Then, place the jar in a planetary ball mill and grind at 1500 rpm for 40 minutes. Discard the mixed powder.

[0049] (2) The mixed powder is poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It is first heated to 600°C at a rate of 5°C / min and pre-fired for 5 hours, then cooled to room temperature in the furnace. It is then reheated to 1000°C and kept at this temperature for 5 hours. After completion, it is cooled to room temperature in the furnace to obtain a fluorescent material.

[0050] Example 9 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.3 Li 0.7 Ga 1.3 Ti 0.7 O4: 0.001Cr 3+ The stoichiometric ratio ( x =0.7). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, titanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material in a ball mill containing an appropriate amount of anhydrous ethanol. Then, place the ball mill in a planetary ball mill and grind at 2000 rpm for 30 minutes. Discard the mixed powder.

[0051] (2) The mixed powder was poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It was first heated to 800°C at a rate of 5°C / min for 4 hours, and then cooled to room temperature in the furnace. It was then reheated to 1100°C and kept at this temperature for 4.5 hours. After completion, it was cooled to room temperature in the furnace to obtain the fluorescent material.

[0052] Example 10 A preparation process of a zinc gallate-based near-infrared long-lasting fluorescent material comprises the following steps: (1) According to Zn 0.1 Li 0.9 Ga 1.1 Ti 0.9 O4: 0.004Cr 3+ The stoichiometric ratio ( x =0.9). Use an analytical balance to accurately weigh zinc oxide, lithium carbonate, gallium oxide, titanium dioxide, and chromium trioxide as raw materials. Combine each weighed raw material in a ball mill containing an appropriate amount of anhydrous ethanol. Then, place the ball mill in a planetary ball mill and grind at 1500 rpm for 30 minutes. Discard the mixed powder.

[0053] (2) The mixed powder was poured into an agate mortar, then transferred to a crucible and placed in a muffle furnace. It was first heated to 700°C at a rate of 5°C / min and pre-fired for 4.5 hours, then cooled to room temperature in the furnace. It was then reheated to 1100°C and kept at this temperature for 4 hours. After completion, it was cooled to room temperature in the furnace to obtain the fluorescent material.

[0054] Figure 7 The X-ray diffraction patterns (XRD) of the fluorescent materials prepared in Examples 6 to 10 show that the fluorescent materials prepared in the above examples have Li + 、Ti 4+ It was successfully doped into ZnGa2O4, and the river crab fluorescent material has good crystallinity, high purity, and no impurities.

[0055] Figure 8 For Examples 6 to 10 and the blank control group (i.e. x =0) prepared by the long afterglow luminescence spectrum of the fluorescent material. It can be seen that: Compared with the blank control group, the fluorescent materials prepared in Examples 6 to 10 are + 、Ti 4+ Co-doping effectively improves the afterglow lifetime, increases the depth of the trap energy level, and stores more electrons. As a result, after the excitation stops, the electrons are slowly released from the trap energy level, effectively suppressing the rate of afterglow decay and increasing the luminescence time and intensity.

[0056] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A zinc gallate-based near-infrared long-lasting fluorescent material, characterized in that: The fluorescent material is composed of Zn 1- x Li x Ga 2-x M x O4: y Cr 3+ , where 0.001≤ y ≤0.005, and when the M is Ge 4+ When 0.1≤ x ≤0.5, when M is Ti 4+ When 0.1≤ x ≤0.

9.

2. The preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 1, characterized in that: The steps include: (1) According to the Zn 1-x Li x Ga 2-x M x O4: y Cr 3+ Weighing a zinc source, a lithium source, a gallium source, a M source, and a chromium source in a stoichiometric ratio as raw materials, mixing these raw materials and grinding them to obtain a mixed powder for later use; (2) The mixed powder is calcined and then cooled to room temperature to obtain the fluorescent material.

3. The preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 2, characterized in that: In step (1), the zinc source includes at least one of zinc carbonate, zinc oxide, etc.

4. The preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 2, characterized in that: In step (1), the lithium source includes at least one of lithium carbonate, lithium oxide, etc.

5. The preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 2, characterized in that: In step (1), the gallium source includes gallium oxide, etc.

6. The preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 2, characterized in that: In step (1), the chromium source includes chromium trioxide and the like.

7. The preparation process of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 2, characterized in that: In step (1), among the M sources, the Ge source includes germanium dioxide and the like, and the Ti source includes titanium oxide and the like.

8. The process for preparing the zinc gallate-based near-infrared long-lasting fluorescent material according to any one of claims 2 to 7, characterized in that: In step (1), the grinding time is 30-40 min, and the grinding rate is 1500-2000 rpm.

9. The process for preparing the zinc gallate-based near-infrared long-lasting fluorescent material according to any one of claims 2 to 7, characterized in that: In step (2), the calcination treatment is carried out as follows: first heating to 600-900°C for pre-calcination for 3-5 hours, then cooling to room temperature with the furnace, then reheating to 1000-1200°C for insulation for 3-5 hours, and then cooling to room temperature with the furnace after completion.

10. Use of the zinc gallate-based near-infrared long-lasting fluorescent material according to claim 1, or the zinc gallate-based near-infrared long-lasting fluorescent material obtained by the preparation process according to any one of claims 2 to 9 in the fields of temperature warning signs, biomedical imaging, night vision displays or lighting.

Citation Information

Cited By

  • Long afterglow nanoparticles, nanoprobe, double-probe system and detection method

    CN120865901A